Economic modelling of CO2 injection for enhanced gas recovery and storage: a reservoir simulation study of operational parameters - Khan, Chawarwan; Amin, Robert; Madden, Gary (Canadian Centre of Science and Education, 2012)
This paper focuses on the recovery factor of natural gas production and storage by injecting CO2 into a natural gas reservoir. This task will be performed by using reservoir simulation software (Roxar-Tempest) with experimental data initially produced by Clean Gas Technology Australia for a known field in North West Shelf Australia. The Optimum case is determined among different cases scenarios as a function of different injection rates, various stages of injection, destination of injection and production wells placement, and various layers in terms of rock qualities “Core Plugs”. In addition, the economic feasibility of CO2 injection for enhanced gas recovery CO2-EGR and storage is valuated in terms development costs, costs associated with the process of CO2 capture and storage as well as carbon credit with considering carbon tax for CO2 storage. The simulation results show that the process of CO2 injection and enhanced natural gas recovery can be technically feasible for this particular reservoir. Occurrence of mixing CO2 with the initial gas in place is inevitable issue, while it can be limited by good reservoir management and production control measurements. Economically, the process of CO2-EGR and storage is affected by many parameters such as CO2 and natural gas prices and carbon tax, while carbon credit still makes the process more attractive.